2022
DOI: 10.1021/acs.langmuir.2c02578
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nanoparticles in Nanofluid Droplet Impact on Solid Surfaces

Abstract: Splashing of a liquid droplet onto a substrate, while ubiquitous, sits at the intersection of several key fluid mechanical regions. Typically, this problem is often simplified to the transition between spreading and splashing, even for splashing on complex surfaces. Recently, there has been increased interest in using not just pure liquids but also nanofluids in applications such as spray cooling. While the addition of a few percent of nanoparticles to a Newtonian fluid does not change its apparent viscosity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Similarly, Aksoy et al observed that the oscillation and retraction of a nanofluid droplet are suppressed . Furthermore, they reported that the presence of nanoparticles, especially hydrophobic ones, alters the droplet’s impact dynamics transition from spreading to splashing by lowering the critical Weber number for splashing. ,, …”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, Aksoy et al observed that the oscillation and retraction of a nanofluid droplet are suppressed . Furthermore, they reported that the presence of nanoparticles, especially hydrophobic ones, alters the droplet’s impact dynamics transition from spreading to splashing by lowering the critical Weber number for splashing. ,, …”
Section: Introductionmentioning
confidence: 93%
“…The addition of nanoparticles into the base fluid induces particle–liquid and particle–particle interactions that influence several liquid properties, such as viscosity, surface tension, and thermal conductivity. ,, Recently, some research has been directed toward the impact of nanofluid droplets on unheated surfaces. ,, When compared to the base fluid, the presence of nanoparticles in nanofluids alters the droplet’s impact dynamics, such as rebound height, ,, spreading diameter, and spreading–splashing boundaries. ,, For example, various researchers have found that nanofluids typically exhibit a lower rebound height than base fluids due to increased viscosity dissipation. , Specifically, Liu et al found that the addition of nanoparticles affects both the spreading and receding velocity of the droplet by changing the fluid’s viscosity . Similarly, Aksoy et al observed that the oscillation and retraction of a nanofluid droplet are suppressed .…”
Section: Introductionmentioning
confidence: 99%
“…Example of a TOC graphic from the Langmuir Perspective article by Aksoy et al titled “Role of Nanoparticles in Nanofluid Droplet Impact on Solid Surfaces” …”
Section: A Research Article At First Glance: Title Abstract and Toc G...mentioning
confidence: 99%
“…As a result of modifications in wettability, selective nanoparticle adsorption on pore surfaces and increases in oil-relative porosity were achieved. , Wasan and Nikolov employed video microscopy in their research to demonstrate how an immiscible fluid spreads through solid surfaces when nanoparticles are present . Surface wetting is brought on by an increase in the nanofluids’ spreading coefficient, an increase in the film pressure toward the wedge’s vertex, and an increase in the separate auxiliary weight. , The presence of a polyacrylamide solution, which improves the hydrophilicity of the SiO 2 NP surface, was attributable to the decrease in the contact angle . The flow component on the shake surface was regarded as an auxiliary disjoining weight.…”
Section: Controlling Factors For the Success Of Nanofloodingmentioning
confidence: 99%